Local Value Manifestation of Joglo Majapahit House In Perspective Learning History and Multicultural Society Dimension In The Rural Bejijong, Mojokerto - Deni Adi Wijaya, Darmawan Edi Winoto & Augustinus Danish Singgih Prabowo (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
This article analyzes the values of local wisdom is wavering because of the falling valueof the character learners as a result of cultural changes leading to modernization. Whilelocal cultural values still exist, although not commensurate with the modernization thatemphasizes instant results. Educational value can be answered about the waning value ofthe character and be able to build a national identity through the values of local wisdom.Local Values are very suitable to be applied in teaching history in Indonesia becausepeople are very diverse as the manifestation Joglo Majapahit. Joglo Majapahit is amanifestation of ancient Javanese culture that includes elements of educational value thatcan be integrated in the learning of history. Joglo Majapahit is a form of religious stylebuilding that represents the relationship Kejawen vertical and horizontal. The verticalrelationship between man and God and Nature while horizontal relationships betweenhumans and other humans. In Mojokerto, Joglo Majapahit very closely linked to the lifeof an agrarian society and religious systems Javanese kingdom of Majapahit period. Thisresearch is conducted in the village of Bejijong, District Trowulan, Mojokerto. Accordingto Henry Maclaine Pont geographical location Bejijong is in the Northern Capital ofMajapahit Kingdom of Wilwatikta (Trowulan). Bejijong village serve the division limitreligious system in the Kingdom of Majapahit between Dharmadhyaksa Ring Kasogatan(regulator Buddhism) is located in Northern Trowulan and Dharmadhyaksa RingKasaiwan (regulator Hinduism) is located in the South side Trowulan. Therefore formJoglo Majapahit is a manifestation of a cultural cauldron of Hindu and Buddhist peoplethat represent the multicultural society. The plurality can be found today because theregion Bejijong are found relics characteristically of Buddhist temples and relics of thetomb characteristically Hindu.Keywords: Joglo Majapahit, Learning History, Local Value, Multicultural Society